Comparable expression of miR-let-7b, miR-21, miR-182, miR-145, and p53 in serum and cervical cells: Diagnostic implications for early detection of cervical lesions: Differential expression of miRNAs in serum and cervical cells - Okoye, Jude Ogechukwu; Ngokere, Anthony A.; Onyenekwe, Charles C.; Erinle, Charles A. (International Journal of Health Sciences, 2019)
Objective: The high mortality associated with cervical cancer is due to low uptake of Pap smear test, lack of early diagnostic biomarkers and less-invasive approach, and late presentation of the disease. This study evaluated the expression of hsa-miR-let-7b, hsa-miR-21, hsa-miR-125b, hsa-miR-143, hsa-miR-145, hsa-miR-146a, hsa-miR-155, hsa-miR-182, hsa-miR-200c, and p53 in serum and cervix in relation to classes of Pap smear, in a bid to identify a serum panel for early diagnosis of cervical lesions. Methodology: This study included 329 women; 159 healthy women (HW), 46 cervicitis, 46 atypical squamous cells of undetermined significance (ASCUS), 40 low-grade squamous cell intraepithelial lesion (LSIL), 28 high-grade squamous cell intraepithelial lesion (HSIL), and 10 squamous cell carcinoma (SCC). Expression of microRNAs (miRNAs) and p53 was assessed using reverse transcriptase polymerase chain reaction. Results: Except for miR-143 and miR-146a, significant correlations were observed between serum and cervix expression of miRNAs and p53 in relation to levels and classes of Pap smear (P < 0.05). Relatively, higher expression of miR-21, miR-146a, miR-155, miR-182, and miR-200c and lower expression of let-7b and miR-145 were observed in sera associated with cervical abnormalities than in sera associated with normal cervix (P < 0.0001, P = 0.001, P < 0.0001, P = 0.003, P = 0.007, P = 0.036, and P = 0.046, respectively). Higher and lower expression of p53 was observed in women diagnosed of LSIL and SCC, respectively, than in HW (P < 0.0001). Conclusion: This study suggests that serum expression of miR-21, miR-182, let-7b, miR-145, and p53 is comparable to cervical cell expression and could be useful in differentiating abnormal cervix from the healthy cervix.